Partial FMRP expression is sufficient to normalize neuronal hyperactivity in Fragile X neurons. (4th February 2020) - Graef, John D.; Wu, Hao; Ng, Carrie; Sun, Chicheng; Villegas, Vivian; Qadir, Deena; Jesseman, Kimberly; Warren, Stephen T.; Jaenisch, Rudolf; Cacace, Angela; Wallace, Owen
Abstract: Fragile X syndrome (FXS) is the most common genetic form of intellectual disability caused by a CGG repeat expansion in the 5′‐UTR of the Fragile X mental retardation gene FMR1, triggering epigenetic silencing and the subsequent absence of the protein, FMRP . Reactivation of FMR1 represents an attractive therapeutic strategy targeting the genetic root cause of FXS. However, largely missing in the FXS field is an understanding of how much FMR1 reactivation is required to rescue FMRP‐dependent mutant phenotypes. Here, we utilize FXS patient‐derived excitatory neurons to model FXS in vitro and confirm that the absence of FMRP leads to neuronal hyperactivity. We further determined the levels of FMRP and the percentage of FMRP‐positive cells necessary to correct this phenotype utilizing a mixed and mosaic neuronal culture system and a combination of CRISPR, antisense and expression technologies to titrate FMRP in FXS and WT neurons. Our data demonstrate that restoration of greater than 5% of overall FMRP expression levels or greater than 20% FMRP‐expressing neurons in a mosaic pattern is sufficient to normalize a FMRP‐dependent, hyperactive phenotype in FXS iPSC‐derived neurons. Abstract : Previous studies have demonstrated that near full restoration of FMRP levels in Fragile X syndrome iPSC‐derived neuronal models can be achieved using gene editing tools; however, the minimum level of FMRP expression needed to normalize functional differences has not been established. In this study, we have confirmed a spontaneous, electrically hyperactive FXS phenotype in multiple iPSC‐derived neuronal lines. We then used CRISPR gene editing, cell mixing models, ASO‐mediated knockdown of FMR1 and targeted demethylation of CGG repeats to demonstrate that partial expression of FMRP can correct the hyperactive phenotype in iPSC‐derived FXS neurons.